Body fluid alterations and organ hypertrophy in age-dependent salt hypertension of Dahl rats - Dobesová, Z; Kunes, J; Zicha, J (Physiological research, 1995)
The relationship between possible alterations in the volume or distribution of extracellular fluid and the development of salt hypertension was studied in inbred salt-sensitive (SS/Jr) and salt-resistant (SR/Jr) Dahl rats. Blood pressure, cardiac and renal hypertrophy as well as body fluid volumes were determined in young and adult SS/Jr and SR/Jr rats of both sexes that were subjected to low, normal or high salt intake for various periods of time. Salt hypertension in young salt-sensitive rats fed a 4% NaCl diet was not accompanied by any substantial intravascular or interstitial expansion as compared to salt-resistant rats that remained normotensive. There was no sex difference in the response of blood pressure or body fluids to high salt intake. Major expansion of plasma and blood volume, which was elicited by 8% NaCl diet feeding from prepuberty, was not accompanied by a further blood pressure rise (compared to salt hypertensive SS/Jr rats fed 4% NaCl diet). In conclusions, salt hypertension can occur in Dahl salt-sensitive rats without major salt and water retention. The degree of intravascular expansion is not directly related to blood pressure levels in salt-loaded Dahl rats. A high salt intake seems to exert its hypertensive effects in Dahl rats preferentially by influencing the balance of vasoconstrictor and vasodilator systems rather than by increasing the haemodynamically active intravascular volume.
Keywords: Animals; Kidney; extracelulární prostor; hypertenze; Body Fluids; Female; Sodium Chloride, Dietary; kuchyňská sůl; inbrední kmeny potkanů; ženské pohlaví; Organ Size; Extracellular Space; Aging; Rats, Inbred Strains; tělesné tekutiny; Plasma Volume; krevní tlak; Sex Characteristics; objem plazmy; Hypertension; velikost orgánu; Male; hypertrofie; pohlavní dimorfismus; stárnutí; krysa rodu Rattus; zvířata; mužské pohlaví; Hypertrophy; Blood Pressure; ledviny; myokard; Myocardium; Rats